The Role of Macrophages in Kidney Fibrosis - Wang, Xiaoling; Chen, Jianwei; Xu, Jun; Xie, Jun; Harris, David C. H.; Zheng, Guoping (Frontiers in Physiology, 2021)
The phenotypic heterogeneity and functional diversity of macrophages give them a complex role in the development and progression of kidney diseases. After kidney injury, bone marrow-derived monocytes are rapidly recruited to the glomerulus and tubulointerstitium to become activated, differentiate into pro-inflammatory M1 macrophages, initiate Th1-type adaptive immune responses, and damage normal tissues. In contrast, M2 macrophages induce Th2-type immune responses, secrete large amounts of TGF-β, transform into αSMA+ myofibroblasts in injured kidney, inhibit immune responses, and promote wound healing and tissue fibrosis. Previous studies on the role of macrophages in kidney fibrosis were mainly focused on inflammation-associated injury and injury repair. Apart from macrophage-secreted profibrotic cytokines, such as TGF-β, evidence for a direct contribution of macrophages to kidney fibrosis is lacking. However, under inflammatory conditions, Wnt ligands are derived mainly from macrophages and Wnt signaling is central in the network of multiple profibrotic pathways. Largely underinvestigated are the direct contribution of macrophages to profibrotic signaling pathways, macrophage phenotypic heterogeneity and functional diversity in relation to kidney fibrosis, and on their cross-talk with other cells in profibrotic signaling networks that cause fibrosis. Here we aim to provide an overview on the roles of macrophage phenotypic and functional diversity in their contribution to pro-fibrotic signaling pathways, and on the therapeutic potential of targeting macrophages for the treatment of kidney fibrosis.